2006
DOI: 10.1016/s0022-5347(05)00919-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Suitable Endogenous Reference Genes for Gene Expression Studies of Human Bladder Cancer

Abstract: For normalization purposes in gene profiling studies of bladder cancer the genes SDH and TBP are recommended as single reference genes depending on the expression level of the target gene or more favorably in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 20 publications
3
103
0
Order By: Relevance
“…Further, using the eight genes as internal reference, we observed that the prognostic accuracy of B2M was 0.82 (95% CI ¼ 0.63 -0.94; data not shown). In a separate study conducted with a small set of tissues (n ¼ 14), we observed that B2M maintained its high prognostic accuracy for lymph node metastases (AUC ¼ 0.79) when more classical reference control genes TBP (Ohl et al, 2006) or UBP (Andersen et al, 2004) were substituted for Spint2 (not shown). Area under the curve values were obtained using the mean C t value of the patient sample as an internal reference.…”
Section: Map7mentioning
confidence: 90%
“…Further, using the eight genes as internal reference, we observed that the prognostic accuracy of B2M was 0.82 (95% CI ¼ 0.63 -0.94; data not shown). In a separate study conducted with a small set of tissues (n ¼ 14), we observed that B2M maintained its high prognostic accuracy for lymph node metastases (AUC ¼ 0.79) when more classical reference control genes TBP (Ohl et al, 2006) or UBP (Andersen et al, 2004) were substituted for Spint2 (not shown). Area under the curve values were obtained using the mean C t value of the patient sample as an internal reference.…”
Section: Map7mentioning
confidence: 90%
“…This issue was investigated by Ohl et al and found that the most commonly used endogenous control GAPDH is not stably expressed in bladder cancer. They found TATA box-binding protein and succinate dehydrogenase complex, subunit A, the most appropriate endogenous control in bladder caner (17). Therefore, we used TATA box-binding protein to normalize our target genes expression.…”
Section: Methodsmentioning
confidence: 99%
“…Cycling parameters were as follows: initial denaturation at 95°C for 12 min; 45 cycles of 1 s at 95°C for denaturation, 5 s at 62°C for annealing and 10 s at 72 °C for extension. Primer sequences were as follows: Axin2-FW: 5'-agtcagcagagggacaggaa-3', Axin2-RW; 5'-agctctgagccttcagcatc-3'; G6PD-FW: 5'-atcgaccactacctgggcaa-3', G6PD-RW: 5'-ttctgcatcacgtcccgga-3' [19]. All primer sequences exclude amplification of genomic DNA under the parameters described above.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%